The current results of the Breast Cancer Screening Program in the State Clinical Hospital of Khanty-Mansiysk - N. A. Zakharova; S. W. Duffy; Ye. V. Kotlyarov; I. P. Gromut; A. V. Philimonov (Опухоли женской репродуктивной системы)
The main aim of this study is to evaluate the current results of the Breast Cancer Screening Program performed in the State Clinical Hospital of Khanty-Mansiysk. The screening covers women over 40 years old. The screening interval is 2 years, with 2-view mammography and single reading as the standard. During 2007– 2010 within the Program, 6980 w omen were screened. The screening coverage rate is the app roxi- mately 55.6 %. 8.3 % of screened w omen were referred for further assessment. The average cancer detection rate w as 5 per 1000 s creened women. The test sensitivity was estimated as 98.2 %. The main criteria are within the international standard’s level.